The Effectiveness of Teacher Ratings in Identifying Potential Intellectually Gifted Malay Children - Mohd Isa, Abd Majid (Universiti Putra Malaysia Press, 1996)
In this study, the effectiveness of the Malay version of scale for rating behaviour characteristics of superior students (SRBCSS) was tested as a potential tool for the identification of intellectually gifted Malay children. Pupils with a score of at least 46 on Raven's standard progressive matrices (Raven's SPM) were given the WISC-R test. Of the 303 respondents, 101 scored a full-scale IQ of 120 or more and were classified as intellectually gifted. Teachers were asked to rate the respondents using the translated version of SRBCSS. The findings of this study suggest that teachers should be given appropriate SRBCSS subtests if they are involved in identifying intellectually gifted children.